Flow cytometry and immune thrombocytopenic purpura. Issue 6 (December 2018) - Goubran, Hadi; Hart, Caroline; Othman, Ibraheem; Seghatchian, Jerard
Abstract: Although Immune thrombocytopenic purpura is a common disorder that family physicians, internists and hematologists face in their everyday practice, its diagnosis rests only on "exclusion" and its therapy is based on algorithms where "trial and error" is the rule. Flow cytometry, if simplified and standardized, could provide a quicker and better diagnostic accuracy. Studies of the lymphocyte subset using flow cytometry and more elaborate immune studies are paving the way for a better understanding of the disease and in identification of prognostic markers. Such studies may even help stratify the first-line therapy responder and assist in the use of the arsenal of immune suppressive therapy with better precision.